Codium fragile Suppressed Chronic PM2.5-Exposed Pulmonary Dysfunction via TLR/TGF-β Pathway in BALB/c Mice - Tae Yoon Kim; Jong Min Kim; Hyo Lim Lee; Min Ji Go; Seung Gyum Joo; Ju Hui Kim; Han Su Lee; Won Min Jeong; Dong Yeol Lee; Hyun-Jin Kim; Ho Jin Heo (MDPI AG, 2023)
This study investigated the ameliorating effect of the aqueous extract of Codium fragile on PM2.5-induced pulmonary dysfunction. The major compounds of Codium fragile were identified as palmitic acid, stearic acid, and oleamide using GC/MS2 and hexadecanamide, oleamide, and 13-docosenamide using UPLC-Q-TOF/MSE. Codium fragile improved pulmonary antioxidant system deficit by regulating SOD activities and reducing GSH levels and MDA contents. It suppressed pulmonary mitochondrial dysfunction by regulating ROS contents and mitochondrial membrane potential levels. It regulated the inflammatory protein levels of TLR4, MyD88, p-JNK, p-NF-κB, iNOS, Caspase-1, TNF-α, and IL-1β. In addition, it improved the apoptotic protein expression of BCl-2, BAX, and Caspase-3 and attenuated the fibrous protein expression of TGF-β1, p-Smad-2, p-Smad-3, MMP-1, and MMP-2. In conclusion, this study suggests that Codium fragile might be a potential material for functional food or pharmaceuticals to improve lung damage by regulating oxidative stress inflammation, cytotoxicity, and fibrosis via the TLR/TGF-β1 signaling pathway.